Randomized, placebo-controlled, double-blind study assessing the efficacy and safety of paliperidone palmitate in Asian patients with schizophrenia - Takahashi N; Takahashi M; Saito T; Iizumi M; Saito Y; Shimizu H; Matsumura T (Neuropsychiatric Disease and Treatment, 2013)
Nagahide Takahashi,1 Maayoshi Takahashi,2 Takayuki Saito,3 Misuzu Iizumi,4 Yuki Saito,5 Hiroko Shimizu,6 Taka Matsumura7 1Clinical Responsible Physicians Department, Clinical Science Division, 2Clinical Science Initiative Department, Clinical Science Division, 3Project Lead Department, Project Development Division, 4Trial Management Department, Japan Clinical Operations Division, 5Biostatistics Department, Quantitative Science Division, 6Clinical Pharmacology Department, Quantitative Science Division, 7Clinical Science Division, Janssen Pharmaceuticals KK, Tokyo, Japan Background: This 13-week, double-blind study was conducted to confirm the efficacy and safety of paliperidone palmitate (PP), at dosing regimens approved in other countries, in Asian patients with schizophrenia. Methods: Asian patients (aged ≥20 years) diagnosed with schizophrenia (Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition-Text Revision criteria), and having a Positive and Negative Syndrome Scale (PANSS) total score of 60 to 120 were enrolled and randomized (1:1) to a PP or placebo group. Patients received PP intramuscularly at recommended doses: initiation dose 150 mg equivalent (eq) PP on day 1 and 100 mg eq PP on day 8 (deltoid); and a monthly maintenance dose of 75 mg eq PP on days 36 and 64 (deltoid or gluteal). The change from baseline to week 13 in PANSS total scores (primary endpoint), Clinical Global Impression-Severity (CGI-S) scores, and PANSS Marder factor scores and subscales, and responder rate at week 13 were evaluated. Safety was also assessed. Results: The PANSS total score (P<0.0001, least-squares mean change from baseline to week 13: PP, -3.5; placebo, +6.2), CGI-S score (P<0.0001), and PANSS Marder factor scores (P≤0.0025) were significantly improved at week 13 in the PP group versus placebo. More treatment responders (≥30% decrease in PANSS total score) were in the PP group (22.8%) versus placebo (8.5%). Insomnia (PP 17.0% versus placebo 15.2%), injection site pain (13.2% versus 6.7%), nasopharyngitis (12.6% versus 6.1%), psychiatric symptoms (11.3% versus 26.2%), and extrapyramidal symptoms (10.1% versus 4.9%) were the most frequently occurring treatment-emergent adverse events. Conclusion: PP is efficacious for Asian patients with schizophrenia at the dosing regimen approved in other countries, with a similar safety and tolerability profile. Keywords: Asian, paliperidone palmitate, Positive and Negative Syndrome Scale total score